Valeur écologique et produits de cueillette des plantations forestières de la Forêt classée de la Téné - Bi Tra Aimé Vroh; Youssouf Kone (VertigO)
In Côte d’Ivoire, since 1986, the Téné Gazetted Forest has been reforested based of exotic species on more than 21,000 ha for timber production. Botanical inventories in these forest plantations and a remaining natural forest and ethnobotanical surveys have permitted us to assess the ecological and conservation value and the relationships between the neighbouring communities and this timber production system. The remaining forests (109 species) and multi-specific forest plantations (104 species) have higher plant diversity than mono-specific teak plantations. These two habitats are also more stable and have high plant biomass than mono-specific young and old teak plantations. The high abundance of Cedrela odorata, one of the exotic reforestation species in the remaining forest, may require future study about its potential negative impacts on establishing native tree species in the reforested area at Téné Gazetted Forest. More than half (49%) of the harvested products are from the Téné Gazetted Forest; that attests to good collaboration between the forest police officers and the neighbouring communities.